2013
DOI: 10.1007/s11207-013-0298-4
|View full text |Cite
|
Sign up to set email alerts
|

On Ponderomotive Effects Induced by Alfvén Waves in Inhomogeneous 2.5D MHD Plasmas

Abstract: Where spatial gradients in the amplitude of an Alfvén wave are nonzero, a nonlinear magnetic-pressure gradient acts upon the medium (commonly referred to as the ponderomotive force). We investigate the nature of such a force in inhomogeneous 2.5D MHD plasmas by analysing source terms in the nonlinear wave equations for the general case of inhomogeneous B and ρ, and consider supporting nonlinear numerical simulations. Our equations indicate there are two distinct classes of ponderomotive effect induced by Alfvé… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 34 publications
1
31
0
Order By: Relevance
“…All perturbations to variables in theB 0 -andĈ-directions are of O(α 2 ) and smaller, indicating that behaviour detailed in the following paragraphs is nonlinear and that the Alfvén wave is linearly decoupled from the magnetoacoustic waves (as first discussed in Thurgood & McLaughlin 2013a). Figure 3 shows the field-aligned perturbations in |v B |, where we find a nonlinear O(α 2 /2) disturbance that is everywhere cospatial to the Alfvén wave in v A .…”
Section: Proper Null =mentioning
confidence: 58%
See 1 more Smart Citation
“…All perturbations to variables in theB 0 -andĈ-directions are of O(α 2 ) and smaller, indicating that behaviour detailed in the following paragraphs is nonlinear and that the Alfvén wave is linearly decoupled from the magnetoacoustic waves (as first discussed in Thurgood & McLaughlin 2013a). Figure 3 shows the field-aligned perturbations in |v B |, where we find a nonlinear O(α 2 /2) disturbance that is everywhere cospatial to the Alfvén wave in v A .…”
Section: Proper Null =mentioning
confidence: 58%
“…Equation (6) can be derived from Eqs. (2) using the process detailed in Thurgood & McLaughlin (2013a) and is the nondimensionalised equivalent to their Eq. (12).…”
Section: Proper Null =mentioning
confidence: 99%
“…This disturbance is not an independently propagating wave (in β = 0 such motion is prohibited), but a direct consequence of the longitudinal component of the ponderomotive force, which is induced, sustained and carried by the propagating Alfvén wave. This is the specific manifestation of the longitudinal daughter disturbance, a general feature of nonlinear Alfvén waves and a common manifestation of the ponderomotive force (see Thurgood & McLaughlin 2013 for a detailed discussion). Now we consider the fast-mode velocity component v ⊥ , shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A large body of work regarding the ponderomotive A&A 555, A86 (2013) effects of waves in various MHD scenarios has demonstrated that nonlinear Alfvén waves can generate magnetoacoustic waves as they propagate through regions of inhomogeneous Alfvén speed (such as, e.g., Nakariakov et al 1997Nakariakov et al , 1998Verwichte et al 1999;Botha et al 2000;Tsiklauri et al 2001;McLaughlin et al 2011a;Thurgood & McLaughlin 2013). The specific nature of ponderomotive mode conversion is dependent upon the gradients in the amplitude of the pulse and gradients in the Alfvén-speed profile.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation